Current status and influencing factors of prophylactic use of proton pump inhibitors in internal medicine inpatients receiving glucocorticoid therapy - Liu, Pengpeng; Li, Guangyao; Wu, Qian; Han, Mei (Frontiers in Pharmacology, 2024)
The actual situation and influencing factors of prophylactic use of proton pump inhibitors (PPIs) in internal medicine inpatients receiving glucocorticoid therapy are rarely reported. This study aimed to investigate the current status and influencing factors of prophylactic use of PPIs in internal medicine inpatients receiving glucocorticoid therapy to provide a basis for rational prophylactic use of PPIs.: Internal medicine inpatients receiving glucocorticoid therapy from February 2023 to September 2023 were included. Information on the prophylactic use of PPIs was collected and analyzed by clinical pharmacists. Associated factors with prophylactic use of PPIs were analyzed by univariable and multivariable logistic regression. Results: 980 inpatients were finally included in our study, of which 271 (27.7%) inpatients received prophylactic use of PPIs. Among the inpatients prescribed PPIs, 90 inpatients received a standard dose of PPIs twice a day. Multiple logistic regression analysis showed that age ≥ 80 years [OR = 7.009, 95% CI (1.424, 34.495), p = 0.017], history of gastroesophageal reflux disease (GERD) [OR = 2.047, 95% CI (1.338, 3.133), p = 0.001], low platelet count [OR = 0.997, 95% CI (0.994, 0.999), p = 0.004], number of concomitant diseases [OR = 1.104, 95% CI (1.056, 1.153), p ＜ 0.001], junior doctors [OR = 1.755, 95% CI (1.248, 2.468), p = 0.001], glucocorticoid dose (higher than 50mg, measured by methylprednisolone) [OR = 2.455, 95% CI (1.371, 4.395), p = 0.003], antiplatelet agents [OR = 2.567, 95% CI (1.456, 4.524), p = 0.001], immunosuppressants [OR = 1.477, 95% CI (1.014, 2.153), p = 0.042], and betahistine [OR = 5.503, 95% CI (1.124, 26.950), p = 0.035] were associated with more prophylactic use of PPIs. Conclusions: The prophylactic use of PPIs in internal medicine inpatients receiving